Do Size and Value Factors Continue to be Relevant in the Indian Stock Market? - Rabha, Debajit; Singh, Rajkumar Giridhari; Vanlalzawna, C. (Indian Journal of Research in Capital Markets, 2025)
Purpose : This study examined the applicability of the Fama-French three-factor model in the Indian stock market. The model comprised of three independent variables: beta/market risk, size, and value. The study aimed to validate these factors to determine their capacity to elucidate the risk-return relationship in the Indian stock market. Methodology : Three independent variables––namely, market risk (beta), size, and value were considered. Data spanning 16 years was collected from January 2006 to December 2021. Portfolios were constructed using equities from the Nifty 500 index, the 91-day Treasury bill as the risk-free rate, and the Nifty 200 index return used as a proxy for market returns. Findings : The study revealed a significant presence of size in the Indian stock market, according to its findings; however, the influence of value was determined to be minor. Another significant finding that emerged from the investigation was the confirmation that the CAPM does carry some weight. Practical Implications : Investors across diverse categories in the stock market can leverage the current study’s findings when incorporating any stock into their portfolios. Investors may evaluate any single variable or a combination of variables to assess the risk–return trade-off of a specific stock. For instance, investors might select low-beta stocks for less risk, small-cap stocks due to their superior performance compared to large-cap companies, or undervalued stocks that yield more profits than overvalued equities. Originality : Most previous studies concentrated on small datasets. However, the current research utilized a substantial dataset and incorporated key indexed equities, specifically the NSE Nifty 500. A significant discovery, in contrast to prior investigations, was the validation of the beta.